2013
DOI: 10.3109/02699206.2012.752867
|View full text |Cite|
|
Sign up to set email alerts
|

Lexical and child-related factors in word variability and accuracy in infants

Abstract: The present study investigated the effects of lexical age of acquisition (AoA), phonological complexity, age and expressive vocabulary on spoken word variability and accuracy in typically developing infants, aged 1;9-3;1. It was hypothesized that later-acquired words and those with more complex speech sounds would be produced more variably and less accurately than earlier-acquired words and those with less complex speech sounds. It was also hypothesized that word variability would decrease and word accuracy wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
49
3
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(63 citation statements)
references
References 19 publications
9
49
3
2
Order By: Relevance
“…By age 5;0, children exhibited no variable production of affricates at all. These findings are in line with those from studies on intra-word variability that showed that variable production characterises early speech (Holm, Crosbie, & Dodd, 2007;Macrae, 2013;Sosa & Stoel-Gammon, 2006). Moreover, in view of the possible overlap between groups (mentioned above in the ''Method'' section), some caution is needed in interpreting the frequency data shown here, especially in the age range between 4;0 and 4;11, when IWV tends to be an uncommon error type for the production of affricates.…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…By age 5;0, children exhibited no variable production of affricates at all. These findings are in line with those from studies on intra-word variability that showed that variable production characterises early speech (Holm, Crosbie, & Dodd, 2007;Macrae, 2013;Sosa & Stoel-Gammon, 2006). Moreover, in view of the possible overlap between groups (mentioned above in the ''Method'' section), some caution is needed in interpreting the frequency data shown here, especially in the age range between 4;0 and 4;11, when IWV tends to be an uncommon error type for the production of affricates.…”
Section: Resultssupporting
confidence: 88%
“…Vihman & Croft, 2007). Ferguson and Farwell (1975) argued that one among the many sources of variable production can be the presence of harder sounds in the word forms, and studies by McLeod and Hewett (2008) and Macrae (2013) also confirmed the effect of phonemic complexity. Furthermore, in their study on intra-word variability, Leonard and his colleagues found that words with phonological aspects emerging during acquisition resulted in more variable production than those containing non-acquired aspects (Leonard, Rowan, Morris, & Fey, 1982).…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…Intraword variability has most often been used to describe a frequently observed phenomenon in the speech of very young, typically developing children. Factors that have been found to influence how variably a word is produced include word frequency and phonological neighborhood density (Sosa & Stoel-Gammon, 2012) as well as phonological complexity (Macrae, 2013;Sosa & Stoel-Gammon, 2012), with longer words with more complex phonological structures produced with greater variability. Their data include one notable example of a girl, aged 1;4 (years;months), who produced the word pen 10 different ways during one 30-min session.…”
Section: Variability Versus Inconsistencymentioning
confidence: 99%